Transcriptomic and Physiological Responses of the Tropical Reef Calcified Macroalga Amphiroa fragilissima to Elevated Temperature1. Issue 4 (26th April 2021) - Yang, Fangfang; Wei, Zhangliang; Long, Lijuan
Abstract : Calcareous macroalgae are of particular ecological importance as primary producers, carbonate sediment builders, and habitat providers in coral reef ecosystems. Ocean warming is a major threat to calcareous algae, but it remains unclear exactly how these algae will respond to it. In this study, the potential physiological impacts of ocean warming on the calcareous alga Amphiroa fragilissima were evaluated in laboratory experiments. Increasing temperature from 26 to 28°C had positive effects on algal growth rate and chlorophyll a content, but these parameters decreased significantly at 32°C, which is 5°C above the annual mean temperature in the study region. Algal bleaching occurred at 34°C. There were no significant differences in CaCO3 content of thalli among different temperatures; however, calcification rate was inhibited significantly at 32 and 34°C. Transcriptome analyses using the Illumina RNA‐seq platform showed that differentially expressed genes were annotated mainly in the categories of steroid biosynthesis, gap junction, ribosome, and mTOR signaling pathway. The expression levels of Psb A and Psb P were suppressed at 32°C, implying that inactivation of photosystem II could be a main reason for the decreased photosynthetic rate. Down‐regulation of the genes encoding carbonic anhydrase and nitrate reductase was observed at 32°C, which could inhibit growth rate. Additionally, several genes that might be related to calcification were identified, including CAMK, CDPK, and CAM and genes encoding alpha‐catenin and carbonic anhydrase. This study contributes to our understanding of the effects of temperature on algal calcification and provides a theoretical basis to protect ecological diversity of coral reef ecosystems.